Chalkboards to Clicks: A Narrative Study of Flipped English Classrooms in Nepal - Paudel, Pitambar (Exploration अन्वेषण, 2026)
The flipped classroom has progressed across the world, yet ELT remains virtually untouched in Nepal. This narrative inquiry study investigates the experiences of four secondary English teachers in the Kaski district who have taught for over one year with the flipped classroom model. Engaging professionally through semi-structured individual interviews, a focus group discussion, and classroom observations, the study revealed teachers’ stories of resistance, adaptation and pedagogical transformation. The study found that there were many success stories with benefits such as enhancements of student classroom participation, autonomy, and interaction. The study also noted challenges such as inconsistent internet access, low student engagement, teacher-centred pedagogical resistance, heavy teacher workloads, and low access to the internet, devices, education, and training. The study argues that there needs to be more flexible and adaptable programs, and institutional frameworks of support with training programs of a digital literacy orientation. The study called for an increased role of the teacher's voice as a mechanism for educational change to support a more inclusive, adaptable, and sustainable program to support mobile educational materials. The study focused on the flipped classroom pedagogical model in Nepal as a unique program in the ELT.